Gambaran Penerapan Sistem Tanggap Darurat Kebakaran Di Rumah Sakit Islam Jakarta Sukapura - Hifdziyatul Maula; Evi Vestabilivy (STIKes Persada Husada Indonesia, 2020)
The hospital is one place that cannot be separated from various possible fire hazards. Therefore, it is also necessary to make a good emergency response system to fire hazards, provide appropriate emergency response equipment, and conduct periodic trials. Hospital fires have also occurred in Indonesia, including the fire at the Doctor Sardjito General Hospital, Yogyakarta on August 6, 2017, the fire at the Asih Serang Hospital, Banten due to an electrical short circuit on July 29 2009, the fire at the Mintoharjo Navy Hospital, Jakarta in March 2016 due to an electric short circuit that left 4 people dead. The purpose of this study was to determine the description of the application of the Fire Emergency Response System at the Islamic Hospital in Jakarta Sukapura. This research is a qualitative research with the focus of research to find out the description of the application of the Fire Emergency Response System at the Islamic Hospital of Jakarta Sukapura. The study was conducted at the K3 unit of the Islamic Hospital in Jakarta Sukapura, which is located on Jl. Tipar Cakung No.5 Sukapura, North Jakarta from June to July 2018. The data collection technique uses informants and data is collected through in-depth interviews, document review and observation. Overall RSIJ Sukapura has implemented an emergency response system well, which is in accordance with OSHAS 18001. However, some elements of the emergency response system are still not fully in accordance with the Ministry of Health No. 1087/MENKES/SK/VIII/2010 Occupational Health and Safety Standards in Hospitals.